2023
DOI: 10.3390/ijms24087404
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Dietary Plant Compounds on Normal and Tumor Brain Cells in Humans: In Silico and In Vitro Approaches

Abstract: Neuroblastoma can be accessed with compounds of larger sizes and wider polarities, which do not usually cross the blood–brain barrier. Clinical data indicate cases of spontaneous regression of neuroblastoma, suggesting a reversible point in the course of cell brain tumorigenesis. Dual specificity tyrosine-phosphorylation-regulated kinase2 (DYRK2) is a major molecular target in tumorigenesis, while curcumin was revealed to be a strong inhibitor of DYRK2 (PBD ID: 5ZTN). Methods: in silico studies by CLC Drug Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…By MVD simulation (Table 2), the efficacy of 7-Lut (score −128.51) and 8-Lut (score −126.66) in interfering with DYRK2 activity was confirmed; both compounds positioned as stronger inhibitors of 5ZTN in comparison with the native ligand curcumin (score −115.85). Former studies on DYRK2 and 5ZTN [24] indicated luteolin aglycone scores of −71.01 by CLC simulation and −104.91 by MVD simulation; therefore, luteolin aglycone is a weaker 5ZTN inhibitor than curcumin and the two luteolin glycosides as well. Tables 1 and 2 present comparative data on the intermolecular interactions, explicitly hydrogen bonding (HB) between the native ligand curcumin docked in complex with the DYRK2 binding site, in comparison with the two test ligands, 7-Lut and 8-Lut.…”
Section: In Silico Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…By MVD simulation (Table 2), the efficacy of 7-Lut (score −128.51) and 8-Lut (score −126.66) in interfering with DYRK2 activity was confirmed; both compounds positioned as stronger inhibitors of 5ZTN in comparison with the native ligand curcumin (score −115.85). Former studies on DYRK2 and 5ZTN [24] indicated luteolin aglycone scores of −71.01 by CLC simulation and −104.91 by MVD simulation; therefore, luteolin aglycone is a weaker 5ZTN inhibitor than curcumin and the two luteolin glycosides as well. Tables 1 and 2 present comparative data on the intermolecular interactions, explicitly hydrogen bonding (HB) between the native ligand curcumin docked in complex with the DYRK2 binding site, in comparison with the two test ligands, 7-Lut and 8-Lut.…”
Section: In Silico Studiesmentioning
confidence: 98%
“…By MVD simulation (Table 2), the efficacy of 7-Lut (score −128.51) and 8-Lut (score −126.66) in interfering with DYRK2 activity was confirmed; both compounds positioned as stronger inhibitors of 5ZTN in comparison with the native ligand curcumin (score −115.85). Former studies on DYRK2 and 5ZTN [24] indicated luteolin aglycone scores of −71.01 by CLC simulation and −104.91 by MVD simulation; therefore, luteolin aglycone is a weaker 5ZTN inhibitor than curcumin and the two luteolin glycosides as well. * Ligands' structures were retrieved from the PubChem database [25] and submitted to minimization using Molecular Mechanics Force Field (MMFF) [26] using Spartan v. 14 software (Wavefunction, Inc., Irvine, CA, USA); atoms' labeling was randomly chosen by the software.…”
Section: In Silico Studiesmentioning
confidence: 99%
See 1 more Smart Citation